2010
DOI: 10.5251/abjna.2010.1.3.391.394
|View full text |Cite
|
Sign up to set email alerts
|

Mycoflora of copra and effect of brining on some properties of copra in Nigeria

Abstract: Mycoflora of copra cultivars and effect of brining on the preservation of the product was investigated. Brining at 0, 10, 20, 30 and 40% concentrations irrespective of the cultivar, had no significant effect on the total oil contents of the copra, total free fatty acid and iodine value but significantly affected the severity of infection of the mycoflora. Aspergillus niger, Aspergillus Flavus and Rhizopus stolonifer were isolated from the copra cultivars and were found to reduce total oil content, and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 1 publication
7
8
0
Order By: Relevance
“…However, the present investigation indicates that the aforementioned fungi were associated with deterioration of onion bulbs. This agrees with the findings of [3,4] that fungi constitute a menace in the storage of many agricultural commodities including fruits, vegetables and nuts. Finding also showed that all the isolated bacteria were also found to be pathogenic, the highest among of the bacteria in terms of the size of rot is Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the present investigation indicates that the aforementioned fungi were associated with deterioration of onion bulbs. This agrees with the findings of [3,4] that fungi constitute a menace in the storage of many agricultural commodities including fruits, vegetables and nuts. Finding also showed that all the isolated bacteria were also found to be pathogenic, the highest among of the bacteria in terms of the size of rot is Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 92%
“…Fungal and bacterial isolates from the study are similar to those of [4], who also isolated Aspergillus niger, Rhizopus stolonifer and Fusarium oxysporum from the rotten onion bulbs sold at five different markets in Sokoto, Nigeria, [3,5] also implicated fungi as contaminants of many agricultural commodities including onions. Also [6] reported Aspergillus niger as the causative agent of black mold rot of onions while [7], isolated Enterobacter species, Pseudomonas species, Escherichia coli from rotten onion bulbs sold in Uyo Metropolis, Akwa Ibom, Nigeria.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Therefore, the application of cleaning, brining and aseptic handling that characterised the improved fermentation method lowered fungi contamination and growth in the oil. This agrees with the finding of Dimkpa, and Onuegbu, (2010) that cleaning and brine disinfection protocols had no significant effect on the total oil contents of the copra, total free fatty acid and iodine value but significantly affected the severity of infection of the mycoflora. Similarly, Onuegbu and Ihuanne (1994) reported reduction in growth of A. niger, Penicillium spp.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, studies on the effect of extractions methods on quality of vegetable oils had reported alteration in chemical composition and oxidative stability of the oil (Hopia, 1993;Vekiari et al, 2002;Dimkpa and Onuegbu, 2010;Tasan et al, 2011). Fundamentally, in this study the obvious variation in the extraction methods centered on the applications of conditions that improved quality of Also processing steps such as decanting had been reported to be responsible for high acidity in olive oils (Vaz -Freire et al, 2008).…”
Section: Discussionmentioning
confidence: 66%